2021
DOI: 10.1186/s13287-021-02572-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genetically modified platelet-derived growth factor-BB over-expressing mesenchymal stromal cells during core decompression for steroid-associated osteonecrosis of the femoral head in rabbits

Abstract: Background Approximately one third of patients undergoing core decompression (CD) for early-stage osteonecrosis of the femoral head (ONFH) experience progression of the disease, and subsequently require total hip arthroplasty (THA). Thus, identifying adjunctive treatments to optimize bone regeneration during CD is an unmet clinical need. Platelet-derived growth factor (PDGF)-BB plays a central role in cell growth and differentiation. The aim of this study was to characterize mesenchymal stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
2
19
0
1
Order By: Relevance
“…The injection of PDGF-BB-MSCs significantly decreased the number of empty lacunae and increased angiogenesis compared to MSCs. In addition, CD with an injection of PDGF-BB-MSCs had a trend towards greater osteogenic differentiation than the CD alone group [ 47 ]. Regarding osteogenic differentiation in our in vitro studies, the PDGF-BB-MSC group showed the best results among all eight groups.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of PDGF-BB-MSCs significantly decreased the number of empty lacunae and increased angiogenesis compared to MSCs. In addition, CD with an injection of PDGF-BB-MSCs had a trend towards greater osteogenic differentiation than the CD alone group [ 47 ]. Regarding osteogenic differentiation in our in vitro studies, the PDGF-BB-MSC group showed the best results among all eight groups.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive osteoclast activity is important in bone integrity loss and subsequent subchondral bone fracture. A growing literature suggests the presence of hyperactive osteoclasts in vivo ONFH models [ [115] , [116] , [117] , [118] ]. However, exogenous glucocorticoids have been proved to directly impair osteoclast function in vitro [ 119 ].…”
Section: Cell Models For Osteonecrosis Of the Femoral Headmentioning
confidence: 99%
“…As all data on gene-modified MSCs are from animal experiments, the efficiency and safety in patients are not presently known and await evaluation in clinical trials. [36][37][38] Growth factors may be directly implanted in the lesion site to enhance osteogenesis and angiogenesis. However, direct implantation of growth factors is complicated by practical problems of peptide therapy, such as an extremely short half-life and side effects with systemic or high-dose administration.…”
Section: Delivery Of the Cellsmentioning
confidence: 99%